2013
DOI: 10.4111/kju.2013.54.8.547
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Sonic Hedgehog and Epithelial-Mesenchymal Transition in Renal Cell Cancer Progression

Abstract: PurposeSonic hedgehog (Shh) signaling and epithelial-mesenchymal transition (EMT) are both known to relate to cancer progression. The purpose of this study was to investigate the role of Shh signaling and EMT in renal cell carcinoma (RCC).Materials and MethodsCell proliferation was assayed in RCC cell lines in the presence or absence of a Shh signaling stimulator, recombinant Shh (r-Shh) protein, or a Shh signaling inhibitor, cyclopamine. Real-time reverse transcription-polymerase chain reaction (RT-PCR) was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…In this regard, the administration of rhein provided a decent suppressive effect. In addition to its role in fibrogenesis, SHH is suggested as a prominent switch to an accelerated progression of cancer and metastasis (Behnsawy et al , , Grzelak et al , ). In the study of Sherman and Zavros, aberrant SHH expression was found in the development of chronic gastric inflammation and the progression to gastric cancer post H. pylori infection (Sherman and Zavros, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the administration of rhein provided a decent suppressive effect. In addition to its role in fibrogenesis, SHH is suggested as a prominent switch to an accelerated progression of cancer and metastasis (Behnsawy et al , , Grzelak et al , ). In the study of Sherman and Zavros, aberrant SHH expression was found in the development of chronic gastric inflammation and the progression to gastric cancer post H. pylori infection (Sherman and Zavros, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in thyroid cancer, SHH is expressed in 64% of PTC tissues but only in 17% of non-cancerous tissues, and GLI1 is expressed in 48% and 9% of these two different types of tissues, respectively [ 115 ]. Activation of the SHH pathway is related to promotion of the EMT process in lung cancer cell lines [ 116 ], renal cell cancer [ 117 ], and gastric cancer [ 91 ]. Based on these observations, blocking SHH signaling is a popular strategy in cancer therapy.…”
Section: Multiple Signal Transduction Pathway and Their Crosstalksmentioning
confidence: 99%
“…Cyclopamine was discovered to inhibit the Hedgehog signaling pathway by direct binding to the G protein‐coupled receptor Smoothened (Chen et al ., ). As such, cyclopamine has shown promising antineoplastic activities against several cancers in which Hedgehog signaling malfunction is implicated, including pancreatic cancer, renal cell carcinoma, medulloblastoma, basal cell carcinoma, and leukemia (Gailani et al ., ; Taipale et al ., ; Berman et al ., ; Olive et al ., ; Lin et al ., ; Bahra et al ., ; Behnsawy et al ., ). A semi‐synthetic analog of cyclopamine, IPI‐926, has been in clinical trials for treatment of several cancers including pancreatic cancer and leukemia (Olive et al ., ; Tremblay et al ., ; Lin et al ., ).…”
Section: Introductionmentioning
confidence: 97%